Community Economic Development Through Diversification and Pineapple Processed Product Packaging Technology: Peningkatan Ekonomi Masyarakat Melalui Diversifikasi dan Teknologi Pengemasan Produk Olahan Nenas - Indah Sari, Vonny; Ulfa Azzahro, Hanifah; Harmaidi, Desma (Universitas Lancang Kuning, 2024)
Pineapples are a potential commodity in Kampar Regency, specifically in Kualu Nenas Village, Tambang District. This activity is based on the problems faced by pineapple SMEs who only sell fresh pineapples on the roadside and some of them are processed into pineapple chips. The solution offered by the service team is the diversification of processed pineapple products, packaging technology that packages processed pineapple products better, practically, safely from contaminants, and guaranteed quality. In addition, with digital marketing strategies through social media, the marketing of processed pineapple products can reach a wider area. The method of service used is a comprehensive presentation on the diversification of pineapple processing products, packaging technology, product quality assurance, and Good Manufacturing practices that ensure the processing complies with applicable standards, as well as effective and efficient marketing strategies through digital and social media. Next, the practice of making several pineapple processed products and utilizing pineapple peels. The evaluation results of the partners' knowledge improvement from the delivered activity materials reached 92.9%.